Development of Live Liveworksheets-Assisted Teaching Materials Using A Problem-Based Learning Model On Student's Learning Outcomes - Widianti, Devi; Sopyan, Asep; Rahman, Andi; Hidayat, Wahyu (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2024)
Interactive learning can be one solution to attract students' interest in participating in learning activities and help to answer the problem of students' low understanding of mathematics. Liveworksheet is a platform that can be used in the educational sector. This research aims to produce teaching materials that are valid, practical and have the potential to influence improving student learning outcomes. The research method used is the design research model development studies method which aims to develop a product. The subjects of this research were 42 class X students of a private vocational school in the city of Cimahi. The liveworksheets-assisted teaching materials developed are adapted to the steps of the problem-based learning model. First, students are introduced to a contextual problem and then guided through questions that allow students to conclude the results of their analysis. The teaching materials developed have gone through a validation stage from material experts, meaning that the teaching materials are in accordance with the material to be taught. The research results showed that the teaching materials developed were proven valid based on the assessment results of two material expert validators and were proven practical from the results of one-on-one and small-group tests. Data analysis used in this research uses inferential statistics with the type of processing of two dependent samples. The teaching materials developed have been proven to be able to improve students' mathematics learning outcomes when viewed from the Minimum Completeness Criteria.